2006
DOI: 10.1007/bf03022532
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular diastolic dysfunction as predictors of difficult separation from cardiopulmonary bypass

Abstract: Moderate and severe LVDD and RVDD can be identified with very good reproducibility, and both degrees of diastolic dysfunction are associated with DSB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 32 publications
1
47
1
7
Order By: Relevance
“…P REOPERATIVE left ventricular (LV) diastolic dysfunction appears to be a stronger predictor of hemodynamic instability after cardiopulmonary bypass (CPB) compared to systolic dysfunction 1 and more severe diastolic dysfunction present before cardiac surgery is associated with difficult separation from CPB. 2 Moreover, the presence of LV diastolic dysfunction has been shown to be an independent predictor of cardiac events (cardiac death, repeat hospital admission for congestive heart failure or myocardial infarction, and angina pectoris) at one year after coronary artery bypass graft (CABG) surgery. 3 This is clinically important because the prevalence of diastolic dysfunction in elderly and hypertensive patients undergoing cardiac surgery has been estimated to be 30%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…P REOPERATIVE left ventricular (LV) diastolic dysfunction appears to be a stronger predictor of hemodynamic instability after cardiopulmonary bypass (CPB) compared to systolic dysfunction 1 and more severe diastolic dysfunction present before cardiac surgery is associated with difficult separation from CPB. 2 Moreover, the presence of LV diastolic dysfunction has been shown to be an independent predictor of cardiac events (cardiac death, repeat hospital admission for congestive heart failure or myocardial infarction, and angina pectoris) at one year after coronary artery bypass graft (CABG) surgery. 3 This is clinically important because the prevalence of diastolic dysfunction in elderly and hypertensive patients undergoing cardiac surgery has been estimated to be 30%.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously observed that both left and right ventricular diastolic abnormalities were the most common echocardiographic findings in hemodynamically unstable patients after cardiac surgery, 4 and preoperative right ventricular diastolic dysfunction was associated with increased need for vasoactive drug support after surgery. 2,5 Because preoperative left and right ventricular diastolic dysfunction are associated with post-CPB hemodynamic instability, improvement of LV diastolic function could represent an approach to reduce the risk of instability following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…По-прежнему остаются раз-ночтения в эффективности восстановления крово-тока после выполнения операций с ИК и на рабо-тающем сердце. По литературным данным, средняя и тяжелая степени диастолической дисфункции ЛЖ связаны с тяжелым состоянием пациентов при отключении аппарата искусственного кровооб-ращения, требующем подключения инотропных препаратов [50]. Несомненно, важным является установление причин, ухудшающих результат опе раций реваскуляризации миокарда.…”
Section: диастолическая функция при ишемической болезни сердцаunclassified